Diversity of Mangrove Plant for Support Ecotourism Activities in Nature Conservation Forum Putri Menjangan, Pejarakan Buleleng-Bali - GINANTRA, I Ketut; SUASKARA, Ida Bagus Made; JONI, Martin (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.v9.5(29).10, 2018)
This study aims to identify the species of mangrove constituents and determine the zonation of the growing community of mangrove plants from the seaward to the landward zone, of the Nature Conservation Forum (NCF) Putri Menjangan coastal Pejarakan village Buleleng from July to October 2017. Identification of mangrove plant species based on the following characteristics: habitus, root type, fruit shape, inflorescence, leaf shape and leaf arangement. Zoning of mangrove grown is determined from vegetation analysis conducted in 3 zones (front zone, middle zone and back zone) with quadrat method, the area of each square is 20 m x 20 m. Parameters specified in each kwadrat are the density, dominance and frequency of presence of each species. Zoning of mangrove community is determined based on the important value of mangrove plant species. The diversity of the mangrove community is calculated by the Shanon-Wiener Diversity Index. The results of the study identified 13 species of true mangrove plants (mangrove) and 14 mangrove mangrove associates. The dominant species are Sonneratia alba (important value / iv is 98.19), Lumnitzera racemosa ( iv. is 40.75), Rhizophora apiculata ( iv. is 35.53), Rhizophora mucronata ( iv. 33.02), Ceriops decandra ( iv .23.61) and Avicennia marina ( iv. 22.22). The diversity index of mangrove species (H) is 2.07, then it is considered good. The pattern of growing mangrove plants in coastal Pejarakan Buleleng, in general follow the natural pattern of mangrove zonation. Typical characteristics and patterns of growing mangrove zonation become interesting attractions and reference for mangrove area managers in ecotourism development and efforts to conserve mangrove forests.